Cannabis and Intentional Self-injury: a Narrative Review - Denissoff Alexander; Levola Jonna; Niemelä Solja; Mustonen Antti (SPRINGERNATURE, 2025)
Purpose of Review: Observational studies assessing the association of cannabis use with subsequent intentional self-injury have reported mixed findings. Longitudinal studies examining the association of cannabis use with subsequent suicide death are notably rare. Our objective was to review longitudinal studies examining cannabis use and subsequent self-harm, suicide attempt, or suicide death.
Recent Findings: Few population-based studies have focused on self-harm with considerable variability across studies in how this outcome has been operationalized. Studies assessing the association between cannabis use and suicide attempt are equivocal in their conclusions and heterogenous in terms of samples utilized and assessment of confounding bias. The results of one meta-analysis were suggestive of dose dependency. For suicide death, the findings are inconsistent, and there is reason for concern of selection bias.
Summary: The existing evidence base on these associations is not yet rigorous enough to allow drawing conclusions on causality. However, cannabis might be seen as an adverse prognostic marker for intentional self-injury.